2018
DOI: 10.1094/pdis-10-17-1569-re
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Management of Invasive Shot Hole Borer and Fusarium Dieback in California Sycamore (Platanus racemosa) in Southern California

Abstract: Fusarium dieback (FD) is a new vascular disease of hardwood trees caused by Fusarium spp. and other associated fungal species which are vectored by two recently introduced and highly invasive species of ambrosia beetle (Euwallacea spp. nr. fornicatus). One of these ambrosia beetles is known as the polyphagous shot hole borer (PSHB) and the other as the Kuroshio shot hole borer (KSHB). Together with the fungi that they vector, this pest–disease complex is known as the shot hole borer–Fusarium dieback (SHB-FD) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Both borers are currently rated “Q” by the California Department of Food and Agriculture, indicating that more information is needed before they can be correctly rated. Most research on KSHB and PSHB to date has focused on controlling the borers, especially in agricultural and urban settings (Dodge et al, 2017; Mayorquin et al, 2018) and on describing their fungal symbionts (Freeman et al, 2013; Na et al, 2018). The borers causing the damage in the riparian habitats of the Tijuana River Valley were collected and identified as the KSHB by Dr. Akif Eskalen at University of California Riverside (UCR), and specimens have been stored in the UCR collection.…”
Section: Methodsmentioning
confidence: 99%
“…Both borers are currently rated “Q” by the California Department of Food and Agriculture, indicating that more information is needed before they can be correctly rated. Most research on KSHB and PSHB to date has focused on controlling the borers, especially in agricultural and urban settings (Dodge et al, 2017; Mayorquin et al, 2018) and on describing their fungal symbionts (Freeman et al, 2013; Na et al, 2018). The borers causing the damage in the riparian habitats of the Tijuana River Valley were collected and identified as the KSHB by Dr. Akif Eskalen at University of California Riverside (UCR), and specimens have been stored in the UCR collection.…”
Section: Methodsmentioning
confidence: 99%
“…Control methods of FD include removal of infested trees followed by chipping or the use of systemic pesticides as part of integrated pest management strategies [14]. However, since restrictions regarding the use of agrochemicals for avocado export and consumption [15] must be considered, further research efforts should focus on environmentally friendly alternatives for the management of FD.…”
Section: Responsible Editor: Lucy Seldinmentioning
confidence: 99%
“…4), and they will provide useful information to inform land managers and the public to help prevent additional movement of infested material. Some potential pesticide treatment options have been researched, including injection and spray applications with insecticides, fungicides, and a biopesticide on sycamore in California (Mayorquin et al 2018), with some found to be effective in reducing further infestation of the beetles compared with the controls. These provide arborists, nurseries, and land managers with options to prevent further infestation.…”
Section: Discussionmentioning
confidence: 99%